Emotion Recognition Following Pediatric Traumatic Brain Injury: Longitudinal Analysis of Emotional Prosody and Facial Emotion Recognition - Schmidt, Adam T. (2010)
Children with closed head injuries often experience significant and persistent disruptions in their social and behavioral functioning. Studies with adults sustaining a traumatic brain injury (TBI) indicate deficits in emotion recognition and suggest that these difficulties may underlie some of the social deficits. The goal of the current study was to examine if children sustaining a TBI exhibit difficulties with emotion recognition in terms of emotional prosody and face emotion recognition and to determine (1) how these abilities change over time and (2) what, if any, additional factors such as sex, age, and socioeconomic status (SES) affected the findings. Results provide general support for the idea that children sustaining a TBI exhibit deficits in emotional prosody and face emotion recognition performance. Further, although some gains were noted in the TBI group over the two-years following injury, factors such as SES and age at injury influenced the trajectory of recovery. The current findings indicate the relationship between TBI and emotion recognition is complex and may be influenced by a number of developmental and environmental factors. Results are discussed in terms of their similarity to previous investigations demonstrating the influence of environmental factors on behavioral recovery following pediatric TBI, and with regard to future investigations that can further explore the link between emotion recognition deficits and long-term behavioral and psychosocial recovery.